Enhanced Photocatalytic Activity of Reduced Graphene Oxide/Bismuth Sulfide Nanostructure Composites for the Degradation of Methylene Blue. (15th September 2021) - Chufa, Bayisa Meka; Gonfa, Bedasa Abdisa; Anshebo, Teketel Yohannes
Abstract : Today, the issue of the environment is the concern of scientists worldwide. Aside from developed countries, developing countries are revolutionizing their economy from agriculture to industries, aggravating the discharge of pollutants. Textile industries are the main sources of pollutant dyes such as methylene blue (MB). In this study, a simple and green synthesis method was used to manufacture a nanostructure heterogeneous photocatalyst, rGO-Bi2 S3, for the degradation of MB. Bi2 S3 and rGO were synthesized separately using Vernonia amygdalina (VA) plant extract. rGO-Bi2 S3 was synthesized using a single-step refluxed hydrothermal method. The products were characterized by XRD, FT-IR, UV-Vis, DTA, TGA, and visual techniques. The comparative degradability degree of the dye under visible light irradiation with and without the presence of the catalyst was studied. The performance test results showed 99% degradation of MB in the presence and 7% in the absence of the catalyst under the same condition for the duration of 25 minutes. The durability and reusability tests for the catalyst were also studied for five cycles. The maximum decrease in the degradation capacity of the catalyst for the duration of 25 minutes was 0.5%. Hence, rGO-Bi2 S3 is found to be the ideal material for the degradation of MB, for environmental protection.